Synthesis, Spectral Characterization, and Antibacterial and Antifungal Studies of PANI/V2O5 Nanocomposites - Chakradhar Sridhar; Nagesh Gunvanthrao Yernale; M. V. N. Ambika Prasad (International Journal of Chemical Engineering)
The present study deals with the synthesis and characterization of nanocrystalline vanadium pentoxide (V2O5) nanoparticles and their antibacterial and antifungal activity on Staphylococcus aureus and Aspergillus niger, respectively, by agar diffusion method. The metal oxide has been synthesized by employing the sol-gel method, polyaniline (PANI) has been synthesized by chemical oxidation, and PANI/V2O5 composites have been synthesized by in situ polymerization method with different ratios (10, 20, 30, 40, and 50 weight%) of V2O5 in PANI. The newly prepared composites were characterized by FTIR and powder X-ray diffraction (P-XRD) techniques and are found to be formed of PANI/V2O5 nanocomposites, and also the compounds showed moderate antibacterial and antifungal activity.